Proceedings of 38th International Cosmic Ray Conference — PoS(ICRC2023) 2023
DOI: 10.22323/1.444.0429
|View full text |Cite
|
Sign up to set email alerts
|

Sibyll$^\bigstar$: ad-hoc modifications for an improved description of muon data in extensive air showers

Abstract: Current simulations of air showers produced by ultra-high energy cosmic rays (UHECRs) do not satisfactorily describe recent experimental data, particularly when looking at the muonic shower component relative to the electromagnetic one. Discrepancies can be seen in both average values and on an individual shower-by-shower basis. It is thought that the muonic part of the air showers isn't accurately represented in simulations, despite various attempts to boost the number of muons within standard hadronic intera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…But we demonstrated here that various data set favor a sligth isospin symmetry breaking with up to 20% more 𝜌 0 than charged 𝜌. As a consequence, the number of muons would be increased by almost 25% as shown in here and in [11]. The lack of precise data do not allow a definitive answer on the exact amount of 𝜌 0 in string fragmentation.…”
Section: Tanguy Pierogmentioning
confidence: 62%
See 1 more Smart Citation
“…But we demonstrated here that various data set favor a sligth isospin symmetry breaking with up to 20% more 𝜌 0 than charged 𝜌. As a consequence, the number of muons would be increased by almost 25% as shown in here and in [11]. The lack of precise data do not allow a definitive answer on the exact amount of 𝜌 0 in string fragmentation.…”
Section: Tanguy Pierogmentioning
confidence: 62%
“…In the following we will call this hadronization "noIB" standing for "no Isospin Breaking". In [11] it is shown that an ad-hoc replacement of 𝜋 0 by 𝜌 0 has a strong influence on muon production because 𝜌 0 decays into charged pions changing significantly the value of 𝑅. But this would break the isospin symmetry, which is based on the assumption that light mesons are massless, which is not the case.…”
Section: Hadronization and Air-shower Physicsmentioning
confidence: 99%